1999
DOI: 10.1192/bjp.174.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of substance misuse in first-episode psychosis

Abstract: This study confirms high rates of substance misuse at onset of psychosis. There is evidence for an increase in diagnosis of substance-related psychotic disorders over time. Those most at risk of substance misuse are young males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
123
6
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(157 citation statements)
references
References 17 publications
20
123
6
8
Order By: Relevance
“…The finding in this study of a prevalence of 45.3% of DD is within the range found by some authors (Cantwell et al, 1999;Margolese et al, 2004), although it should be not- ed that other studies report lower prevalences. For example, Brady et al (1991) found that 29 out of 100 patients admited to a psychiatric unit for acute cases met the DSM-III-R criteria for SUD in the 30 days prior to their admission.…”
Section: Discussionsupporting
confidence: 69%
“…The finding in this study of a prevalence of 45.3% of DD is within the range found by some authors (Cantwell et al, 1999;Margolese et al, 2004), although it should be not- ed that other studies report lower prevalences. For example, Brady et al (1991) found that 29 out of 100 patients admited to a psychiatric unit for acute cases met the DSM-III-R criteria for SUD in the 30 days prior to their admission.…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, this study suggests the need for greater attention to the prevalence, impact, and treatment of SUDs in HD. Given the similarity of these findings to studies on primary psychiatric syndromes where SUDs seem particularly associated with male gender, greater psychiatric morbidity, and earlier age of illness onset (Cantwell et al, 1999;Dixon, 1999;RachBeisel et al, 1999;Siegfried, 1998), further research on HD as a dual diagnosis condition with relatively well-defined genetic and neurobiological origins is warranted. Table 1 Demographics ( (36) 111 (62) 235 (58) 275 (71) Female 645 (64) 69 (38) 172 (42) 110 (29) Marital status Married 773 (77) 124 (69) 288 (71) 251 (65) Separated/divorced…”
Section: Discussionmentioning
confidence: 99%
“…(Cantwell et al, 1999;Veen et al, 2004;Henquet et al, 2005;Mauri et al, 2006;Koskinen et al, 2010;Mazzoncini et al, 2010;Barrigón et al, 2010). Several studies on schizophrenia have reported that patients with SUD have worse premorbid social functioning (Sevy et al, 2010;Mazzoncini et al, 2010;Compton et al, 2011;Schimmelmann et al, 2011), more severe symptoms at onset (Gearon and Bellack, 2000;Dawe et al, 2011), lower compliance and worse treatment response, thus more inappropriate use of mental health services, (Lambert et al, 2005;de Haan et al, 2007;Schimmelmann et al, 2011) with higher mental health costs (Bartels et al, 1993).…”
Section: Introductionmentioning
confidence: 99%